Genealogical abstracts from 18th century Virginia newspapers - Headley, Robert K. (Genealogical Publishing Co., Inc. Baltimore, 1987)
The data abstracted herein have been collected from over 7,100 issues of eighty-one 18th-century Virginia newspapers."--Introd.
Keywords: Registers of births, etc. -- 18th century -- Virginia; American newspapers -- Virginia; Genealogy -- Virginia